Factors Associated with the Unmet Need for Family Planning in Couples of Childbearing Age in Masaloka Raya District, Bombana Regency - Herlina; Binekada, I Made Christian; Tosepu, Ramadhan (International Journal of Sciences: Basic and Applied Research (IJSBAR), 2021)
Unmet need for family planning (FP) is defined as a group of people whose contraceptive needs have not been met, including all men or women of childbearing age who are married or living together who are considered sexually active and do not use contraceptive methods, both those who do not want to have more children or who are postponing next birth. The purpose of the study was to determine the relationship between income, the role of Family Planning Field Officers (FPFO), and the availability of contraceptives with the incidence of unmet need for family planning in Masaloka Raya District, Bombana Regency. The type of research used is survey research using a cross sectional study design. The number of samples is 79 respondents. The technique of determining the sample size is by purposive proportional random sampling. Data collection techniques with interview and observation methods. The instrument used in data collection by using a questionnaire. Data analysis using chi square test. The results showed that there was no relationship between income and the incidence of unmet need for family planning with p value = 0.211> 0.05. There is no relationship between the role of FPFO and the incidence of unmet need for family planning with p value = 0.135> 0.05. There is a relationship between the availability of contaceptives and the incidence of unmet need for family planning with p value = 0.039> 0.05. Conclusion; There is no relationship between income, the role of FPFO with the incidence of unmet need for family planning and there is a relationship between the availability of contraceptives and the incidence of unmet need for family planning. Suggestion; It is hoped that the community will increase income, increase the role of officers to be more active in conducting socialization, counseling and education activities to the community and increase the availability of contraceptives in family planning service units.